Acoustic reciprocity in the spherical harmonic domain: A formulation for directional sources and receivers - Xu, Zeyu; Herzog, Adrian; Lodermeyer, Alexander; Habets, Emanuël; Prinn, Albert G. (JASA Express Letters, 2022)
Acoustic reciprocity states that the transfer function between a source and a receiver remains unchanged if the two are interchanged. An extension of acoustic reciprocity to the spherical harmonic domain has been derived in the literature between a directional source and a directional receiver. The present letter derives a reciprocal relation between source and receiver directivity coefficients, which facilitates the derivation of a transfer function in the spherical harmonic domain using directivity coefficients obtained via reciprocity. Additionally, reciprocity between transfer functions is extended for more general source and receiver directivities, which include acoustic scattering effects.
CRIS-Team WoS Importer:2023-01-06

AmbiSep: Joint Ambisonic-to-Ambisonic Speech Separation and Noise Reduction - Herzog, Adrian; Chetupalli, Srikanth Raj; Habets, Emanuël (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2023)
Blind separation of the sounds in an Ambisonic sound scene is a challenging problem, especially when the spatial impression of these sounds needs to be preserved. In this work, we consider Ambisonic-to-Ambisonic separation of reverberant speech mixtures, optionally containing noise. A supervised learning approach is adopted utilizing a transformer-based deep neural network, denoted by AmbiSep. AmbiSep takes mutichannel Ambisonic signals as input and estimates separate multichannel Ambisonic signals for each speaker while preserving their spatial images including reverberation. The GPU memory requirement of AmbiSep during training increases with the number of Ambisonic channels. To overcome this issue, we propose different aggregation methods.The model is trained and evaluated for first-order and second-order Ambisonics using simulated speech mixtures. Experimental results show that the model performs well on clean and noisy reverberant speech mixtures, and also generalizes to mixtures generated with measured Ambisonic impulse responses.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Ambisonics; Decoding; Encoding; Memory management; noise reduction; Reverberation; reverberation; Speech processing; speech separation; Training; Transformers; transformers

Blind single-channel dereverberation using a recursive maximum-sparseness-power-prediction-model - Herzog, Adrian; Habets, Emanuël (2018 16TH INTERNATIONAL WORKSHOP ON ACOUSTIC SIGNAL ENHANCEMENT (IWAENC), 2018)
CRIS-Team WoS Importer:2019-02-27

Direction and Reverberation Preserving Noise Reduction of Ambisonics Signals - Herzog, Adrian; Habets, Emanuël (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2020)
Ambisonics encodes the directional information of a sound field w.r.t. a reference position in an efficient and scalable way. However, the sound field might contain undesired noise. Reducing the noise while preserving the directional distribution of all sound field components is a challenging task. Recently, the present authors proposed a direction-preserving noise reduction method for higher-order Ambisonics (HOA) signals, which, in contrast to e.g. binaural beamforming methods, yields a HOA signal at the output. In this work, we investigate the direction-preserving noise reduction method further and compare it against a beamforming-based method and the matrix multi-channel Wiener filter. Different methods to estimate the power spectral densities which are needed for the noise reduction methods are discussed. Moreover, a method to preserve the reverberation of the desired signal is proposed. In the evaluation, the discussed methods are compared for different speech sources in anechoic and reverberant conditions and different noise types.
CRIS-Team WoS Importer:2020-09-11

Direction preserving Wiener matrix filtering for Ambisonic input-output systems - Herzog, Adrian; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2019)

DIRECTION PRESERVING WIND NOISE REDUCTION OF B-FORMAT SIGNALS - Herzog, Adrian; Mirabilii, Daniele; Habets, Emanuël (2021 IEEE INTERNATIONAL CONFERENCE ON ACOUSTICS, SPEECH AND SIGNAL PROCESSING (ICASSP 2021), 2021)
CRIS-Team WoS Importer:2021-11-26

Distance estimation in the spherical harmonic domain using the spherical wave model - Herzog, Adrian; Habets, Emanuël (Applied Acoustics, 2022)
Compact spherical microphone arrays are often used to record 3D sound scenes and are well suited to estimate the directions of sound sources. However, estimating the distance of a sound source is a chal-lenging task due to the small dimensions of compact microphone arrays. In this work, different spherical harmonic domain distance estimation methods that utilize the spherical wave propagation model are investigated. Two existing methods are discussed and a new distance estimation method is proposed, which utilizes recurrence relations of spherical Hankel functions. The proposed estimator is related to the ratio between the real and imaginary components of the intensity vector for first-order spherical har-monic domain signals. In addition, a frequency averaging method is proposed and investigated for broad-band distance estimation. Finally, the existing and proposed methods are evaluated using simulated anechoic and reverberant scenarios, as well as spherical microphone array recordings in outdoor and indoor environments.(c) 2022 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2022-06-10

Eigenbeam-ESPRIT for DOA-vector estimation - Herzog, Adrian; Habets, Emanuël (IEEE Signal Processing Letters, 2019)

Gauge invariant canonical cosmological perturbation theory with geometrical clocks in extended phase-space - A review and applications. - Giesel, Kristina; Herzog, Adrian (International Journal of Modern Physics D, 2018)
The theory of cosmological perturbations is a well elaborated field. To deal with the diffeomorphism invariance of general relativity one generally introduces combinations of the metric and matter perturbations which are gauge invariant up to the considered order in the perturbations. For linear cosmological perturbations one works with the so-called Bardeen potentials widely used in this context. However, there exists no common procedure to construct gauge invariant quantities also for higher order perturbations. Usually, one has to find new gauge invariant quantities independently for each order in perturbation theory. With the relational formalism introduced by Rovelli and further developed by Dittrich and Thiemann, it is in principle possible to calculate manifestly gauge invariant quantities, that is quantities that are gauge invariant up to arbitrary order once one has chosen a set of so-called reference fields, often also called clock fields. This article contains a review of the relational formalism and its application to canonical general relativity following the work of Garcia, Pons, Sundermeyer and Salisbury. As the starting point for our application of this formalism to cosmological perturbation theory, we also review the Hamiltonian formulation of the linearized theory for perturbations around FLRW spacetimes. The main aim of our work will be to identify clock fields in the context of the relational formalism that can be used to reconstruct quantities like the Bardeen potential as well as the Mukhanov-Sasaki variable. This requires a careful analysis of the canonical formulation in the extended ADM-phase space where lapse and shift are treated as dynamical variables. The actual construction of such observables and further investigations thereof will be carried out in our companion paper.<br
Keywords: Canonical cosmological perturbation theory; relational framework; gauge invariance; general relativity; Dirac observables.

Gauge invariant variables for cosmological perturbation theory using geometrical clocks - Giesel, Kristina; Herzog, Adrian; Singh, Parampreet (Classical and Quantum Gravity, 2018)
Using the extended ADM-phase space formulation in the canonical framework we analyze the relationship between various gauge choices made in cosmological perturbation theory and the choice of geometrical clocks in the relational formalism. We show that various gauge invariant variables obtained in the conventional analysis of cosmological perturbation theory correspond to Dirac observables tied to a specific choice of geometrical clocks. As examples, we show that the Bardeen potentials and the Mukhanov-Sasaki variable emerge naturally in our analysis as observables when gauge fixing conditions are determined via clocks in the Hamiltonian framework. Similarly other gauge invariant variables for various gauges can be systematically obtained. We demonstrate this by analyzing five common gauge choices: longitudinal, spatially flat, uniform field, synchronous and comoving gauge. For all these, we apply the observable map in the context of the relational formalism and obtain the corresponding Dirac observables associated with these choices of clocks. At the linear order, our analysis generalizes the existing results in canonical cosmological perturbation theory twofold. On the one hand we can include also gauges that can only be analyzed in the context of the extended ADM-phase space and furthermore, we obtain a set of natural gauge invariant variables, namely the Dirac observables, for each considered choice of gauge conditions. Our analysis provides insights on which clocks should be used to extract the relevant natural physical observables both at the classical and quantum level. We also discuss how to generalize our analysis in a straightforward way to higher orders in the perturbation theory to understand gauge conditions and the construction of gauge invariant quantities beyond linear order.<br
Keywords: general relativity; cosmological perturbation theory; Dirac observables

Generalized intensity vector and energy density in the spherical harmonic domain: Theory and applications - Herzog, Adrian; Habets, Emanuël (The Journal of the Acoustical Society of America, 2021)
The acoustic intensity vector and energy density are perceptually relevant physical measures of a sound field that can be used in the context of sound field reproduction or acoustic parameter estimation. In this work, weighted spatial averaging of the intensity vector and energy density is investigated, and the results are expressed in terms of the spherical harmonic coefficients of the sound field. Higher-order spherical harmonic coefficients are incorporated by considering radial averaging. This radial averaging is then generalized, yielding the proposed generalized intensity vector and energy density. Direction-of-arrival and diffuseness estimators are constructed based on the generalized intensity vector and energy density. In the evaluation, the proposed parameter estimators are compared to existing state-of-the-art estimators using simulated signals containing directional, diffuse, and sensor-noise components.
CRIS-Team Scopus Importer:2021-07-30

Geometrical Clocks in Cosmological Perturbation Theory - Herzog, Adrian; Giesel, Kristina (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)

Lie-Punktsymmetrien erhaltende Quantisierung in der Loop-Quantenkosmologie - Giesel, Kristina; Herzog, Adrian (2014)

On the relation between DoA-vector eigenbeam ESPRIT and subspace pseudointensity-vector - Herzog, Adrian; Habets, Emanuël (European Signal Processing Conference, 2019)
Eigenbeam ESPRIT (EB-ESPRIT) is a subspace based method to estimate directions-of-arrival (DOAs) of sound sources from a spherical microphone array recording in the spherical harmonics domain (SHD). In recent works, nonsingular EB-ESPRIT methods have been proposed which can estimate the source DOA-vectors without ambiguities. In another recent publication, a subspace based pseudointensity-vector method (SS-PIV) has been proposed for DOA estimation. In this work, we derive the mathematical relation between the DOA-vector EB-ESPRIT and the SS-PIV method. We show that the SS-PIV can be seen as a special case of the DOA-vector EB-ESPRIT. Using this relation, we propose a novel DOA-estimator denoted as extended pseudointensity-vector (PIV). In the evaluation, we compare the DOA-vector EB-ESPRIT and the extended PIV with the SS-PIV and PIV under noisy and reverberant conditions.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Direction-of-arrival estimation; Eigenbeam ESPRIT; Subspace pseudointensity-vector

Signal-Dependent Mixing for Direction-Preserving Multichannel Noise Reduction - Herzog, Adrian; Habets, Emanuël (29TH EUROPEAN SIGNAL PROCESSING CONFERENCE (EUSIPCO 2021), 2021)
CRIS-Team WoS Importer:2022-04-22

Transient-To-Noise Ratio Restoration of Coded Applause-Like Signals - Adami, Alexander; Herzog, Adrian; Disch, Sascha; Herre, Jürgen (IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2017)
Coding of signals with high amount of dense transient events, like applause, rain drops, etc., is usually a difficult task for perceptual audio coders. Especially at low bit rates, coding (and the associated coding noise) leads to smeared transients and a perceived increase in noise-like signal character. We propose a post-processing technique for coded/decoded applause-like signals which is based on a signal decomposition into foreground (transient) clap events and a more noise-like background part. The proposed method aims at restoring the transient-To-noise ratio of the decoded signal using a static frequency-dependent restoration profile. The method is shown to provide a significant improvement in subjective audio quality (MUSHRA score) when applied to signals originating from a state-of-The-Art audio codec in different configurations.
herre_papers_applause
Keywords: Applause restoration; enhancement; transient separation